Pencegahan Penyakit Tidak Menular (PTM) melalui Health literacy Berbasis Pemberdayaan Kader Posbindu - Parellangi, Andi; Prayogi, Bisepta; Rizani, Khairir; Rasyid, Muhammad (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
The problems that occur in Guntung Paikat Village are related to the high cases of hypertension, namely the community-based health effort (UKBM) container, namely the number of Integrated Development Posts (Posbindu) is only 2, and double as Integrated Development Post (Posbindu) cadres so that their role is not optimal. The objectives of this community service activity are to increase the quantity and quality of Integrated Development Post (Posbindu) containers and increase knowledge, attitudes, and skills about the duties, functions, and roles of Posbindu cadres. Increasing health literacy in terms of knowledge, attitudes, and behaviour about preventing non-communicable diseases, especially hypertension and diabetes mellitus. The method of implementing this community service activity was carried out in Guntung Paikat Village, Banjarbaru City, which was divided into 4 (four) stages, namely the first stage was recruiting Posbindu cadres, the second stage was training cadres, the third stage was providing education and health services to target groups, and the fourth stage was creating a Posbindu container. The results of the community service activities include the recruitment of 15 cadres, and from the 15 cadres, after the training, experienced an increase in knowledge and skills in carrying out Posbindu activities. The conclusion of this community service activity is the increase in knowledge, attitudes, and skills of partners through the Prevention of Non-Communicable Diseases (PTM) through Health Literacy based on the Empowerment of Posbindu Cadres in Guntung Paikat Village. Increasing the independence of cadre partners and families in the community to maintain family health so that non-communicable diseases such as hypertension and diabetes mellitus do not occur, preventing and lowering blood pressure and blood sugar levels in the community.